Mestre Navas, J.M. & Fernández Berrocal, Pablo (2015). Manual de inteligencia emocional. Madrid: Ediciones Pirámide - Reyes de Cózar, Salvador (Revista Fuentes, 2016)
Mestre Navas, J.M. & Fernández Berrocal, Pablo (2015). Manual de inteligencia emocional. Madrid: Ediciones Pirámide